PENGARUH UMUR PEMOTONGAN TERHADAP KADAR AIR, ABU, DAN LEMAK KASAR Indigofera zollingeriana - Aulia, Farah; Erwanto, Erwanto; Wijaya, Agung Kusuma (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
The aim of research to know the effect of cutting age on moisture, ash, and crude fat of Indigofera zollingeriana. The study was done based on Completely Randomized Design (CRD) with 3 treatments and 4 replications. The treatments in this study were : 1) U40 (40 days of cutting age), 2) U50 (50 days of cutting age), and 3) U60 (60 days of cutting age). Indigofera zollingeriana being cuts for the first time at 1 m height from the ground surface and plots of land measuring 3 x 3 m2 and is harvested at a different age. The results showed that the effect of cutting age significantly (P < 0.01) affect moisture, ash, and crude fat of Indigofera zollingeriana. Moisture content of Indigofera zollingeriana with cutting age of 40, 50, and 60 days were 82,37%, 81,28 %, and 77,54% respectively. Ash content of Indigofera zollingeriana with cutting age of 40, 50, and 60 days were 9,72%, 10,51%, and 11,57% respectively. Crude fat content of Indigofera zollingeriana with cutting age of 40, 50, and 60 days were 6,85%, 7,51%, and 10,86% respectively. Key word : Indigofera zollingeriana, cutting age, moisture, ash, and crude fat.